2017
DOI: 10.1039/c6sm01375a
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive microgels at the air–water interface: the impact of the swelling state on interfacial conformation

Abstract: Poly(N-vinylcaprolactam) (PVCL) is a new temperature-responsive type of polymer microgel with improved biocompatibility as compared to more commonly used poly(N-isopropylacrylamide) (PNIPAM). Both polymers swell at low temperatures and collapse at high ones, showing a volume phase transition temperature (VPTT) around the physiological temperature. Exploring the interfacial characteristics of thermoresponsive microgels is important due to their potential application in emulsion based systems with tailored stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 49 publications
1
29
1
Order By: Relevance
“…So far, the effects that an interfacial confinement induces on such particles have been mainly limited to the study of their characteristic shape, and hence, to their structural arrangement at oil-water and air-water interfaces. These aspects have been widely investigated experimentally [30,31] and, more recently, also numerically [29,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…So far, the effects that an interfacial confinement induces on such particles have been mainly limited to the study of their characteristic shape, and hence, to their structural arrangement at oil-water and air-water interfaces. These aspects have been widely investigated experimentally [30,31] and, more recently, also numerically [29,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The most studied microgels are prepared by batch polymerization. It has been earlier demonstrated that such microgels are able to adsorb spontaneously at any temperature [13][14][15][16] giving rise to a sensible decrease of the interfacial tension. It is also known that such microgels are able to stabilize emulsions [17][18][19][20].…”
Section: ) Introductionmentioning
confidence: 99%
“…To achieve effective packing densities of well above the random close packing limit for hard spheres, the reduction in available volume must be accommodated by either shape or volume changes in the constituent particles. This can occur either by forming facets at the contact points with the surrounding particles 8 , 14 , 15 and by the expulsion of solvent from the particle, leading to homogeneous deswelling and volume reduction 16 , 17 . Recent work has highlighted how the latter can have pronounced effects on the interpretation of experiments on microgels, since osmotic deswelling can lead to substantial deviations between the apparent and real particle volume fraction 18 .…”
Section: Introductionmentioning
confidence: 99%